Alteration in Leukocyte Subsets and Expressions of FcγR and Complement Receptors among Female Ragpickers in Eastern India - Nandan K. Mondal; Shabana Siddique; Madhuchanda Banerjee; Sanghita Roychoudhury; Sayali Mukherjee; Mark S. Slaughter; Twisha Lahiri; Manas R. Ray (Elsevier, 2017)
Background: There are a million ragpickers in India who gather and trade recyclable municipal solid wastes materials for a living. The objective of this study was to examine whether their occupation adversely affects their immunity. Methods: Seventy-four women ragpickers (median age, 30 years) and 65 age-matched control housemaids were enrolled. Flow cytometry was used to measure leukocyte subsets, and leukocyte expressions of Fcγ receptor I (CD64), FcγRIII (CD16), complement receptor 1 (CD35) and CR3 (CD11b/CD18), and CD14. Serum total immunoglobulin-E was estimated with enzyme-linked immunosorbent assay. Results: Compared with the controls, ragpickers had significantly (p < 0.0001) higher levels of CD8+T-cytotoxic, CD16+CD56+natural killer, and CD4+CD45RO+memory T-cells, but depleted levels of CD19+B-cells. The percentage of CD4+T-helper-cells was lower than the control group (p < 0.0001), but their absolute number was relatively unchanged (p = 0.42) due to 11% higher lymphocyte counts in ragpickers. In ragpickers, the percentages of CD14+CD16+intermediate and CD14dim CD16+nonclassical monocyte subsets were elevated with a decline in CD14+CD16-classical monocytes. The expressions of CD64, CD16, CD35, and CD11b/CD18 on both monocytes and neutrophils, and CD14 on monocytes were significantly higher in ragpickers. In addition, ragpickers had 2.7-times more serum immunoglobulin-E than the controls (p < 0.0001). After controlling potential confounders, the profession of ragpicking was positively associated with the changes. Conclusion: Ragpicking is associated with alterations in both innate (neutrophils, monocytes, and natural killer cell numbers and expression of complement and Fcγ receptors) and adaptive immunity (numbers of circulating B cells, helper, cytotoxic, and memory T cells).